PENDAMPINGAN KELAS IBU HAMIL DI WILAYAH KERJA PUSKESMAS LAULENG KOTA PAREPARE - Haniarti Haniarti; Ayu Dwi Putri Rusman; Fitriani Umar; Syamsul Rijal Tabang; Suci Tri Ananda (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the main reasons why breast milk is so important is that it is very beneficial for babies in their early life. Lack of knowledge from parents, busy mothers, and reluctance to breastfeed their babies make the achievement of exclusive breastfeeding in Watang Soreang Village, the working area of the Lauleng Health Center, has not met the target. So far, many mothers do not breastfeed their babies because they feel that their milk is not enough, watery or does not come out at all. Whereas according to WHO research there are only one in a thousand people who can not breastfeed. The purpose of this service activity is to assist the class of pregnant women to provide education about the benefits of Early Initiation of Breastfeeding (IMD) and Exclusive Breastfeeding. In addition to providing material, the distribution of IMD Leaflets and Exclusive Breastfeeding was also carried out to further increase the knowledge of pregnant women. This activity was attended by 10 pregnant women in Bukit Harapan Village, Parepare City. The method of implementing the activity uses the principles of the Adult Learning Approach (BOD), namely lectures, questions and answers, demonstrations and practices that are expected to be able to optimize the increase in knowledge and skills of pregnant women regarding exclusive breastfeeding so that later during childbirth they want to do IMD and give exclusive breastfeeding to their babies